Dos especies nuevas de Crassulaceae del sur de Jalisco, México - Jimeno-Sevilla, H. David; Santana Michel, Francisco J.; Carrillo-Reyes, Pablo (Instituto de Ecología, A.C., 2015)
Based on collections from the southern part of the state of Jalisco, Echeveria rulfiana and Villadia ramirezii are described as new species. The former is assigned to series Gibbiflorae and compared with E. marianae, E. novogaliciana, and E. nayaritensis, from which it differs mainly by its caulescent habit and oblanceolate and canaliculate leaves. The latter is related with V. platystyla and can be distinguished by possesing smaller flowers arranged in loose cymes. Both species are narrow endemic elements of southern Jalisco and their conservation statuses are discussed.